Evaluation of Clinical Variables Associated with Increased Carotid Intima-Media Thickness in Middle-Aged Hypertensive Women. (3rd June 2012) - Trindade, Michelle; Martucci, Renata Brum; Burlá, Adriana K.; Oigman, Wille; Neves, Mario Fritsch; Araújo, Denizar Vianna
Abstract : It has been previously documented that carotid intima-media thickness (cIMT) is a predictor of cardiovascular disease. The aim of this study was to identify clinical parameters associated with an increased cIMT treated hypertensive women. Female patients (n = 116 ) with essential hypertension, aged 40–65 years, were included in this study. Vascular ultrasound was performed and the patients were divided into two groups according to the values of cIMT (< or ≥0.9 mm). Patients with greater cIMT presented significantly higher systolic blood pressure and pulse pressure. Serum HDL-cholesterol was significantly lower and CRP was significantly higher in the same group. There was a significant correlation between cIMT and age (r = 0.25, P = 0.007 ), systolic blood pressure (r = 0.19, P = 0.009 ), pulse pressure (r = 0.30, P = 0.001 ), and LDL-cholesterol (r = 0.19, P = 0.043 ). cIMT was correlated to CRP (r = 0.31, P = 0.007 ) and negatively correlated to HDL-cholesterol (r = 0.33, P = 0.001 ). In logistic regression, only HDL-cholesterol, CRP, and pulse pressure were shown to be independent variables associated to increased cIMT. In conclusion, pulse pressure, HDL-cholesterol, and CRP are variables correlated with cIMT in treated hypertensive women.